Investigation of platelet apoptosis in adult patients with chronic immune thrombocytopenia. Issue 3 (16th March 2017) - Deng, Gang; Yu, Shifang; Li, Qiming; He, Yunlei; Liang, Wei; Yu, Lu; Xu, Deyi; Sun, Tao; Zhang, Ri; Li, Qiang
ABSTRACT: Objectives : Immune thrombocytopenia (ITP) is an acquired and heterogeneous autoimmune-mediated hematological disease typically characterized by a low platelet count. Emerging evidence over the past several years suggests that platelet biogenesis and ageing are regulated, at least in part, by apoptotic mechanisms. However, the association between decreased platelets and apoptosis in ITP patients is poorly understood. To better understand the role of platelet apoptosis in ITP pathophysiology, we investigated apoptotic markers in platelets acquired from 40 chronic ITP patients. Furthermore, the results of ITP patients were compared to those from 40 healthy individuals. Methods : Markers of apoptosis, including phosphatidylserine (PS) exposure and mitochondrial inner membrane potentials (ΔΨ m ), were examined using flow cytometry. The expression of pro-apoptotic molecules such as Bak and Bax and anti-apoptotic molecules such as Bcl-xL were determined using quantitative real-time PCR (qRT-PCR) and Western blotting. Results : Our study demonstrated that the platelet mitochondrial membrane depolarization in chronic ITP patients tended to be higher than in healthy controls. Additionally, the proportion of platelets with surface-exposed PS in chronic ITP was significantly higher than that of controls. The results showed that the expression levels of Bak and Bax were significantly higher in chronic ITP patients than in healthy controls; Bcl-xL expression levels were significantly decreased in the platelets of chronic ITP patients compared to healthy controls. Discussion and conclusion : study indicates that the enhancement of platelet apoptosis observed in patients with chronic ITP may be one of the pathogenic mechanisms of chronic ITP.